Continuous co-digestion of sewage sludge and highly concentrated waste bioplastic hydrolyzate without shortening hydraulic retention time - Shinya Akimoto; Jun Tsubota; Taira Hidaka; Taku Fujiwara (Waste Management Bulletin, 2024)
Bioplastics have garnered substantial interest as alternatives to conventional petroleum-based plastics. However, their management and conversion to biogas continues to be significantly challenging. In this study, we evaluated the suitability of various plastics for hydrolysis at 160 °C for 12 h using different solvents. The biogas yield (BGY) of the monomers constituting these plastics and the obtained plastic hydrolyzates was comprehensively evaluated. When water was used as a solvent, 100 % hydrolysis of polylactic acid (PLA) and polybutylene succinate (PBS) was observed. When polybutylene adipate co-terephthalate (PBAT) and polyhydroxybutyrate (PHB) were hydrolyzed with water, the degradation ratio was approximately 30 %; however, using an aqueous lactic acid solution as a solvent improved the degradation ratio to 78 % and 100 %, respectively. In the BGY test of the plastic hydrolyzates, the biogas volumes derived from the hydrolyzates were 563, 461, 337, and 573 mL/g COD-added for PLA, PBS, PBAT, and PHB, respectively. With 1,160 gCOD/L waste PLA hydrolyzate, continuous co-digestion of sewage sludge and the hydrolyzate was conducted. Organic loading rates of sewage sludge and the hydrolyzate were 2.3 and 2.4 gCOD/L/d, respectively. The operation was stable and the methane production volume from the PLA hydrolyzate was 414 L/kgCOD-added. Using highly concentrated PLA hydrolyzate, the hydraulic retention time was 19.3 days, which was only 0.7 days shorter than that of anaerobic digestion of sewage sludge only (20 days). Therefore, highly concentrated PLA hydrolyzate maintains the retention time of normal sewage sludge digestion. Conclusively, the present study has crucial practical implications for plastic waste management.